2013
DOI: 10.1002/dc.23015
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing breast ductal carcinoma in situ on fine‐needle aspiration: A diagnostic dilemma

Abstract: In this study, we evaluated cytomorphologic features of different subgroups of ductal carcinoma in situ (DCIS); we compared seven cytologic features between DCIS and invasive ductal carcinoma (IDC) aspirates to determine whether diagnosis of stromal invasion can be made based on fine-needle aspiration (FNA) findings. There were 142 cases of DCIS and 1,978 cases of IDC enrolled in our study. FNA analysis revealed 80.3% sensitivity for DCIS and 94.7% sensitivity for IDC. High and intermediate grade DCIS exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Bonzanini et al [24],in their study of DCIS versus IDC, reported that tubular clusters were associated with IDC grade 1-2 in 89% of the cases. Guo et al [25 ]remarked on the exclusive association of tubular structures with invasive carcinoma, but that this finding was uncommon (11.5%). Our findings concur with these 2 studies.…”
Section: Discussionmentioning
confidence: 99%
“…Bonzanini et al [24],in their study of DCIS versus IDC, reported that tubular clusters were associated with IDC grade 1-2 in 89% of the cases. Guo et al [25 ]remarked on the exclusive association of tubular structures with invasive carcinoma, but that this finding was uncommon (11.5%). Our findings concur with these 2 studies.…”
Section: Discussionmentioning
confidence: 99%
“…The protein wash seen in cystic change can be confused with serum or the wet background associated with DCIS. Necrosis can produce a fluid like sample but ghost cells and nuclear debris should heighten suspicion and not be confused with a cystic background . Difficulties can arise when extracellular mucin associated with mucinous breast lesions is mistaken for a cystic background.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 39 These stromal changes and hyperproliferative epithelium are similar to the changes observed with ductal carincoma in situ of the breast, leading to the speculation that defective apoptotic cell clearance may provide a catalyst for breast cancer development. 53 , 54 , 55 , 56 , 57 In addition, the immunosuppressive immune milieu associated with clearance of apoptotic cells by the mammary epithelium has also been proposed to contribute to breast cancer progression. 58 , 59 Women have a transient increase in breast cancer risk during the postpartum period and breast cancers diagnosed postpartum have poor prognosis.…”
Section: Discussionmentioning
confidence: 99%